The ‘Other’ in the design project: fashion reports (Revista de Ensino em Artes, Moda e Design, 2020)
This article reports the methodological experience in two design disciplines in the Bachelorin Fashion Design course. In both cases, the project is carried out from the meeting withpeople who are not from the area. Following the conception that design is an interdisciplinaryfield, multiple voices are fundamental for the formation of a designer who works on buildinga more fair and respectful society. In order to theoretically base the methodologies proposedin the disciplines, it starts from participatory design up to contemporary lines, which seek toexpand both ways of making design and its fields of activity.
Keywords: desing project; participatory desing; fashion desing